2011
DOI: 10.1080/01431161.2010.512939
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi-temporal SPOT NDVI images for small-scale land-use mapping

Abstract: Land-use information is required for a number of purposes such as to address food security issues, to ensure the sustainable use of natural resources and to support decisions regarding food trade and crop insurance. Suitable land-use maps often either do not exist or are not readily available. This article presents a novel method to compile spatial and temporal land-use data sets using multi-temporal remote sensing in combination with existing data sources. Satellite Pour l'Observation de la Terre (SPOT)-Veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Other studies have discussed and demonstrated that using hyper-temporal normalized difference vegetation index (NDVI) image datasets is particularly suitable to map (agro-) ecosystems, exploiting their ability to capture aspects of vegetation phenology and crop calendar characteristics (Gorham 1998, Murakami et al 2001, Uchida 2001, Hill and Donald 2003, de Bie 2004, de Bie et al 2008, 2011, Sakamoto et al 2009, Khan et al 2010.…”
Section: Hyper-temporal Ndvi Imagesmentioning
confidence: 98%
“…Other studies have discussed and demonstrated that using hyper-temporal normalized difference vegetation index (NDVI) image datasets is particularly suitable to map (agro-) ecosystems, exploiting their ability to capture aspects of vegetation phenology and crop calendar characteristics (Gorham 1998, Murakami et al 2001, Uchida 2001, Hill and Donald 2003, de Bie 2004, de Bie et al 2008, 2011, Sakamoto et al 2009, Khan et al 2010.…”
Section: Hyper-temporal Ndvi Imagesmentioning
confidence: 98%
“…In China, an increasing number of studies have been carried out to map vegetation types using Pan et al 2003;Wang & Tenhunen 2004;Xiao et al 2005;Jiang et al 2008). Several recent studies have confirmed that SPOT-VGT NDVI and moderate-resolution imaging spectroradiometer (MODIS) NDVI imagery can be used to produce the required land-cover and vegetation maps at various scales (Bagan et al 2007;Matsuoka et al 2007;Fu et al 2010;de Bie et al 2011;Nguyen et al 2012). In this study, we aimed to map at macro-habitat scale the fraction of evergreen forest and the presence probability of epiphyllous liverworts using time-series SPOT-VGT NDVI imagery, and to assess the quantitative relationship between the fraction of evergreen forest and the presence probability of epiphyllous liverworts.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we generated a stratification layer based on the unsupervised classification of NDVI images from eMODIS (see Section 2.2.2), applying an unsupervised clustering algorithm, namely the Iterative Self-Organizing Data Analysis Technique (ISODATA), similar to the approach of de Bie et al [43]. The aim was to obtain a biophysical stratification purely relying on RS data.…”
Section: Linear Regression Model and Spatial Aggregation Levelsmentioning
confidence: 99%